Pengaruh Model Problem Based Learning Berbantuan Media Audiovisual dalam Keterampilan Membaca Siswa Kelas VII SMP Negeri 2 Bayang - hastuti, Sri Oktari; Afnita, Afnita (Journal of Education Language and Innovation, 2024)
This research aims to analyze the influence of the problem-based learning model assisted by audiovisual media in learning reading skills for SMP Negeri 2 Bayang class VII students. The background to this research is the low reading skills of students caused by a lack of motivation and ineffective learning models. The method used is quantitative, with an experimental design for a posttest-only control group. The research instrument is an objective test of descriptive text reading skills. The research results show that the reading skills of students who use the problem-based learning model assisted by audiovisual media are classified as good, with an average of 78.04. In contrast, the reading skills of students who use the project-based learning model are classified as fair, with an average of 62.15. The t-test shows that the alternative hypothesis is accepted at a significance level of 95%, and the tcount value is greater than the ttable value (5.04 > 1.69), which shows that the problem-based learning model assisted by audiovisual media has a significant effect on students' reading skills. This research recommends applying this learning model consistently to improve student's reading skills, especially in learning descriptive texts.